(untitled) (Palimpsesto, 2025)
Motherhood in autistic women has been scarcely studied, largely due to prejudices and stigmas that undermine its legitimacy. This study used phenomenological interviews to analyze the experiences of 12 women in Chile, focusing on their perceptions of the health system during pregnancy and the first two years of parenting. Multiple barriers were identified, including inadequate treatment, violence, lack of support, unfriendly environments, discrimination, and the absence of reasonable accommodations. Isolated positive experiences were also reported. Mothers engaged in masking their autism and normalized inappropriate practices. There is an urgent need to train health teams, develop technical guidelines, and ensure compliance with existing regulations.